Violent conflict and inequality - Cagatay Bircan; Tilman Brück; Marc Vothknecht (Institute for the Study of Labor (IZA), 2010)
This paper analyzes the distributive impacts of violent conflicts, which is in contrast to previous literature that has focused on the other direction. We use cross-country panel data for the time period 1960-2005 to estimate war-related changes in income inequality. Our results indicate rising levels of inequality during war and especially in the early period of post-war reconstruction. However, we find that this rise in income inequality is not permanent. While inequality peaks around five years after the end of a conflict, it declines again to pre-war levels within the end of the first post-war period. Lagged effects of conflict and only subsequent adjustments of redistributive policies in the period of post-war reconstruction seem to be valid explanations for these patterns of inequality. A series of alternative specifications confirms the main findings of the analysis.
Keywords: O11; O15; 330; Conflict; war; inequality; reconstruction; income distribution; Krieg; Kriegsfolgen; Verteilungswirkung; Einkommensverteilung; Schätzung; Welt